2010
DOI: 10.2214/ajr.09.3573
|View full text |Cite
|
Sign up to set email alerts
|

Breast MRI Screening of Women With a Personal History of Breast Cancer

Abstract: We found that breast MRI screening of women with only a personal history of breast cancer was clinically valuable finding malignancies in 12%, with a reasonable biopsy rate (PPV, 39%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
61
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(69 citation statements)
references
References 26 publications
7
61
0
1
Order By: Relevance
“…Relative reduction in false-positive findings in women with a personal history of breast cancer has also been observed with MR imaging screening (15)(16)(17). Reduction in both background parenchymal enhancement and cystic change at MR imaging have been noted in the previously irradiated breast (18).…”
Section: Discussionmentioning
confidence: 85%
“…Relative reduction in false-positive findings in women with a personal history of breast cancer has also been observed with MR imaging screening (15)(16)(17). Reduction in both background parenchymal enhancement and cystic change at MR imaging have been noted in the previously irradiated breast (18).…”
Section: Discussionmentioning
confidence: 85%
“…Throughout the study period, breast MRI and PET were used quite rarely, with a slight secular trend showing increased use over time. The use of breast MRI in women with prior breast cancer is the subject of ongoing investigation [27].…”
Section: Discussionmentioning
confidence: 99%
“…48,49 For example, in a retrospective study of 1,699 patients with a personal history of breast cancer and no other risk factors, Brennan et al 50 observed a cancer-detection rate of 12%, of which 59% were detected by MRI alone. MRI screening in this study yielded a positive predictive value of 39%, and the authors concluded that a definite benefit to its use exists in this population.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…MRI screening in this study yielded a positive predictive value of 39%, and the authors concluded that a definite benefit to its use exists in this population. 50 Benefits of MRI screening should be weighed against risks and limitations such as cost. Saadatmand et al 51 performed a large, prospective study evaluating use of MRI screening in patients with familial risk factors and an estimated lifetime risk of breast cancer that was higher than 15%.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%